Identification and expression profiling of neuropeptides and neuropeptide receptor genes in a natural enemy, Coccinella septempunctata - Han, ShunDa; Chen, JunJie; Liu, ZhaoHan; Zhang, MaoSen; Guo, PengHui; Liu, XiaoXiao; Wang, LongRui; Shen, ZhongJian; Zhang, LiSheng (Frontiers in Physiology, 2024)
Neuropeptides and their receptors constitute diverse and abundant signal molecules in insects, primarily synthesized and released primarily from neurosecretory cells within the central nervous system (CNS). Neuropeptides act as neurohormones and neuromodulators, regulating insect behavior, lifecycle, and physiology by binding to receptors on cell surface. As a typical natural predator of agricultural pests, the lady beetle, Coccinella septempunctata, has been commercially mass-cultured and widely employed in pest management. Insect diapause is a physiological and ecological adaptative strategy acquired in adverse environments. In biological control programs, knowledge about diapause regulation in natural enemy insects provides important insight for improving long-term storage, transportation, and field adoption of these biological control agents.However, little is known about the function of neuropeptides and their receptors in controlling reproductive diapause of C. septempunctata. It is unclear which neuropeptides affect diapause of C. septempunctata. In this study, RNA-seq technology and bioinformatics were utilized to investigate genes encoding neuropeptides and their receptors in female adults of C. septempunctata.Quantitative real-time PCR (qRT-PCR) analysis was employed to examine gene expression across different development/diapause stages. A total of 16 neuropeptide precursor genes and 9 neuropeptide receptor genes were identified, implicated in regulating various behaviors such as feeding, reproduction, and diapause. Prediction of partial mature neuropeptides from precursor sequences was also performed using available information about these peptides from other species, conserved domains and motifs. During diapause induction, the mRNA abundance of AKH was notably higher on the 10th day compared to non-diapause females, but decreased by the 20th day. In contrast, GPHA showed lower expression levels on the 5th day of diapause induction compared to non-diapause females, but increased significantly by the 15th and 20th days. NPF was higher expressed in head and midgut while DH showed higher expression in the fat body and midgut. This study represents the first sequencing, identification, and expression analysis of neuropeptides and neuropeptide receptor genes in C. septempunctata. Our results could provide a foundational framework for further investigations into the presence, functions, and potential targets of neuropeptides and their receptors, particularly in devising novel strategies for diapause regulation in C. septempunctata.